2021
DOI: 10.1038/s41419-021-03394-4
|View full text |Cite
|
Sign up to set email alerts
|

FV-429 induces autophagy blockage and lysosome-dependent cell death of T-cell malignancies via lysosomal dysregulation

Abstract: It is widely accepted that lysosomes are essential for cell homeostasis, and autophagy plays an important role in tumor development. Here, we found FV-429, a synthetic flavonoid compound, inhibited autophagy flux, promoted autophagosomes accumulation, and inhibited lysosomal degradation in T-cell malignancies. These effects were likely to be achieved by lysosomal dysregulation. The destructive effects of FV-429 on lysosomes resulted in blockage of lysosome-associated membrane fusion, lysosomal membrane permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…FV-429 exerts a dual ability to induce apoptosis and autophagy blockage. It was examined in gastric cancers or T-cell malignancies [ 29 , 30 ]. In our research, we focused on relevant proteins involved in the autophagy process: Beclin-1, LC3A, LC3B, and ATG5.…”
Section: Discussionmentioning
confidence: 99%
“…FV-429 exerts a dual ability to induce apoptosis and autophagy blockage. It was examined in gastric cancers or T-cell malignancies [ 29 , 30 ]. In our research, we focused on relevant proteins involved in the autophagy process: Beclin-1, LC3A, LC3B, and ATG5.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of autophagosome or autolysosome may be resulted from the failure at the fusion or degradation phase. 27,28 To address whether DAS impairs the autophagosome-lysosome fusion, we examined the co-localization of GFP-LC3B and LysoTracker red, a dye used to label and track acidic organelles in live cells, such as lysosomes. We found that most GFP-LC3B puncta were not co-localized with LysoTracker red in DAS-treated cells (Figure 4C), indicating that DAS influenced the fusion of autophagosomes and lysosomes.…”
Section: Das Treatment Inhibits Lysosomal Activitymentioning
confidence: 99%
“…Therefore, inducing LMP plays an important regulatory role in LDCD. At present, many LDCD inducers including phenothiazine, flavonoid FV-429, ciprofloxacin or norfloxacin mainly induce LDCD by causing lysosomal damage and LMP 232 , 233 , 234 . Among them, FV-429 can promote LDCD in T cell malignant tumor cells by inducing lysosomal damage and LMP, thereby inhibiting tumor progression 233 .…”
Section: Other Forms Of Non-apoptotic Cell Deathmentioning
confidence: 99%
“…At present, many LDCD inducers including phenothiazine, flavonoid FV-429, ciprofloxacin or norfloxacin mainly induce LDCD by causing lysosomal damage and LMP 232 , 233 , 234 . Among them, FV-429 can promote LDCD in T cell malignant tumor cells by inducing lysosomal damage and LMP, thereby inhibiting tumor progression 233 . Ciprofloxacin (CPX) or Norfloxacin (NFX) can cause LMP and lysosome damage and activate Bax and Bak to cause mitochondrial membrane permeability (MMP) and lysosomal-dependent cell death 232 .…”
Section: Other Forms Of Non-apoptotic Cell Deathmentioning
confidence: 99%